2008
DOI: 10.1111/j.1464-5491.2008.02430.x
|View full text |Cite
|
Sign up to set email alerts
|

Health utility values associated with diabetic retinopathy

Abstract: This study has re-examined the utility decrements associated with DR and has identified much larger declines in utility than previously reported. The study has also reported the utility values of patients with retinopathy as assessed by standard gamble. We believe that this may be the first study to report utility values for health states associated with vision loss which have been elicited from patients with vision loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 26 publications
5
73
2
Order By: Relevance
“…In that sense, our results agree with previous observations by other investigators using the EQ-5D-3L (Langelaan et al 2007;van Nispen et al 2009) and other health utilities instruments (Crewe et al 2011;Briesen et al 2014). In contrast with our results, a study by Lloyd and colleagues found inconsistent associations of utilities with visual acuity in patients with diabetic retinopathy (Lloyd et al 2008). Lloyd obtained lower scores for patients with acuity 6/12 to 6/18 than for patients with acuity 6/24 to 6/36.…”
Section: Discussioncontrasting
confidence: 56%
“…In that sense, our results agree with previous observations by other investigators using the EQ-5D-3L (Langelaan et al 2007;van Nispen et al 2009) and other health utilities instruments (Crewe et al 2011;Briesen et al 2014). In contrast with our results, a study by Lloyd and colleagues found inconsistent associations of utilities with visual acuity in patients with diabetic retinopathy (Lloyd et al 2008). Lloyd obtained lower scores for patients with acuity 6/12 to 6/18 than for patients with acuity 6/24 to 6/36.…”
Section: Discussioncontrasting
confidence: 56%
“…Health state utility weights obtained from the available literature 63 were used to quality adjust the time spent by patients in each visual acuity state, so as to generate QALYs. Health state utilities reflect the relative desirability of different states of health on a scale where zero represents death and one represents full health.…”
Section: Model Overviewmentioning
confidence: 99%
“…In addition, the results are conditional on the model structure and the evidence used to inform it. For example, we used the results from the study by Lloyd et al, 97 which assessed, using the EQ-5D, the utility associated with visual acuity. However, as with the other three studies identified, this association was only available for the best eye (in terms of visual acuity).…”
Section: Figure 19mentioning
confidence: 99%
“…For the model we used the results from the study by Lloyd et al, 97 which assessed, using the European Quality of Life-5 Dimensions (EQ-5D™), the utility associated with visual acuity (as measured using the logMAR scale in the better seeing eye) in 49 patients with diabetes but no retinopathy and 122 patients with DR. The study identified, through multiple regression, that age, disease-specific quality of life (as measured using the National Eye Institute Visual Functioning Questionnaire) and visual acuity were all independent predictors of health utility.…”
Section: Health Utility and Quality-adjusted Life Expectancymentioning
confidence: 99%